On The Sustainability Of Urban Institutional Dynamics: Capitalization, Decentralization, And The Case Of Two Alpine Cities - Church, Jon; Maisetti, Nicolas (Environnement urbain / Urban Environment, 2011)
The focus of this article is on the institutional dimension of urban dynamics, particularly on the twin processes of capitalization – defined as the transformation of a place into a capital city – and decentralization. We observe that they co-exist in several urban contexts. A study was conducted addressing the inherent level of sustainability for each configuration produced by the dynamics. This hypothesis was tested by performing a mental experiment to assess the consequences of the prevalence of one dynamic over the other. To do so, a case study was undertaken on two Italian Alpine cities – Turin and Bolzano – in order to empirically ground the experiment and compare the two conceptual models. From our analysis, both extreme centralization and decentralization seem unsustainable. The broader policy implications are clear: urban institutions must seek to control these processes by avoiding the extremes and mitigating their impacts.